Rapid response to selpercatinib in RET fusion positive pancreatic neuroendocrine carcinoma confirmed by smartwatch - Deschler-Baier, Barbara; Krebs, Markus; Kroiss, Matthias; Chatterjee, Manik; Gundel, Daniel; Kestler, Christian; Kerscher, Alexander; Kunzmann, Volker; Appenzeller, Silke; Maurus, Katja; Rosenwald, Andreas; Bargou, Ralf; et al. (npj Precision Oncology, 2024)
This case report describes the efficacy of selpercatinib, a selective RET inhibitor, in an unusual case of large-cell neuroendocrine pancreatic carcinoma (LCNEPAC) harboring a CCDC6::RET fusion. A 56-year-old male with a history of multiple lines of systemic therapies exhibited marked clinical amelioration shortly after initiating selpercatinib within the LOXO-RET-17001 study (ClinicalTrials.gov ID: NCT03157128, first posted: 2017-05-17). Data from the patient’s smartwatch suggested early efficacy before conventional methods, such as serum tumor markers and CT imaging confirmed the antitumor activity. This case not only underscores the efficacy of selpercatinib in treating RET fusion-positive rare tumors but also highlights the potential of wearable technology in cancer care. In conclusion, the standard readings from commercially available wearable devices can be useful for the monitoring of treatment response to targeted therapy and may serve as digital biomarkers in clinical trials. This approach marks a significant advancement in patient-centric healthcare, leveraging technology to enhance the effectiveness and precision of treatment evaluation.
CRIS-Team Scopus Importer:2025-12-15